2018
DOI: 10.1002/2017gl076790
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the T Phase Energy Fluxes Recorded on Juan Fernandez Island by Continental Seismic Wave Paths and Nazca Bathymetry

Abstract: T phases from 54 South American earthquakes with Mw > 5.2 are observed at a broadband station on Juan Fernandez Island. We computed the T phase energy flux (TPEF) values of the seismograms. The TPEF values show a large dispersion that can be explained by considering the tectonic characteristics of the South American plate and the Nazca plate bathymetry. The TPEFs generated by the 2015 Illapel and 2017 Valparaíso seismic sequences were controlled by the positions of the interface events along the dip. The centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…T waves propagate largely in the form of the lowest available vertical mode, which has a frequency-dependent structure: High-frequency modes are more narrowly confined to the SOFAR channel axis, whereas low-frequency modes span a substantial portion of the water column (28). T-wave arrivals usually have a high signal-to-noise ratio in a frequency range of 1 to 10 Hz (23,24,30,31). To maximize the sensitivity in the deep ocean, we filter the DGAR T-wave seismograms to the lowest-possible frequency band of 1.5 to 2.5 Hz (Fig.…”
Section: T Pmentioning
confidence: 99%
“…T waves propagate largely in the form of the lowest available vertical mode, which has a frequency-dependent structure: High-frequency modes are more narrowly confined to the SOFAR channel axis, whereas low-frequency modes span a substantial portion of the water column (28). T-wave arrivals usually have a high signal-to-noise ratio in a frequency range of 1 to 10 Hz (23,24,30,31). To maximize the sensitivity in the deep ocean, we filter the DGAR T-wave seismograms to the lowest-possible frequency band of 1.5 to 2.5 Hz (Fig.…”
Section: T Pmentioning
confidence: 99%
“…One must note that apart from the Kish Island where numerous, long tremors were reported likely due to a similar mechanism as described above, no similar signals were documented in the north, that is, Iran. To our knowledge, no broadband stations capable of recording the high‐frequency T ‐waves (>50 Hz) were deployed near the Iranian shorelines at the time of the earthquake and thus comparison of the divers' signal with onland seismic records is not possible (see Sáez & Ruiz, 2018 and Text S17 in Supporting Information ). The two closest Iranian seismic stations to the epicenter (i.e., LAR and LMD; see Text S1 in Supporting Information ) are more than 120 km away along complex elastic paths reaching >2,000 m altitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Single‐station analyses of travel time and polarization are feasible to identify T waves. It was confirmed that T waves can be converted from the S waves via analyses of travel time (Lin, 2001; Sáez & Ruiz, 2018). With these methods, the T‐P and T‐S phases were identified in the Alboran Sea (Carmona et al., 2015).…”
Section: Identification Of T‐p and T‐s Phasesmentioning
confidence: 89%
“…The energy of the T phase, generally generated by marine earthquakes, is coupled into the ocean seafloor near the source and converted to seismic waves at the continental slope. The T phase does not depend only on the earthquakes' magnitude, but also on the depth where earthquakes occur, the continental slope, the conversion location, and the conversion efficiency (Carrasco et al, 2019;De Caro et al, 2020;Lin, 2001;Sáez & Ruiz, 2018). Moreover, the mechanism of conversion/coupling is complex, even though model summation (de Groot-Hedlin & Orcutt, 1999, 2001a and ray theory (Chen et al, 2017) 4° to the coast (Buehler & Shearer, 2015), indicating that crustal attenuation structures in the inner stable continent (e.g., >4° from the coast) are difficult to invert with the method proposed in this study.…”
Section: Smentioning
confidence: 99%
See 1 more Smart Citation